2012
DOI: 10.1063/1.4729134
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based photonic crystal to steer giant Faraday rotation

Abstract: We present a graphene-based photonic-crystal schematic of enhancing and steering Faraday rotation angle of graphene. This concept is counter-intuitive because the giant Faraday rotation and high transmission can be simultaneously pronounced, which is distinguished from exisitng graphene structures reported before. It is found that chemical potential can be tailored to generate a controllable giant Faraday rotation via graphene with atomic thickness. By engineering the individual component thickness in the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Peculiar electronic properties have gained increasing interest from many researchers [4][5][6][7][8][9]. A single sheet of undoped graphene has single pass absorption of πα (2.3%), where α¼e 2 /(ħc) is the quantum electrodynamics fine structure constant [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Peculiar electronic properties have gained increasing interest from many researchers [4][5][6][7][8][9]. A single sheet of undoped graphene has single pass absorption of πα (2.3%), where α¼e 2 /(ħc) is the quantum electrodynamics fine structure constant [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, graphene has potential applications in transformation optics and plasmonics [9][10][11]. Recently, it has been theoretically and experimentally demonstrated that graphene can be a good candidate in magneto-optics [12][13][14][15][16][17][18]. The Faraday effect is one of the famous magneto-optical effects in which the polarization plane of light propagating through either a metal or a dielectric rotates in the presence of an external magnetic field along the propagation direction.…”
Section: Introductionmentioning
confidence: 99%
“…Da and Liang have designed a photonic crystal infiltrated with graphene to obtain further enhancement in FR angle [15]. Da and Qiu also have shown that large FR angle and high transmission can be achieved simultaneously in graphene-based photonic crystals [16]. They found that the FR of graphene can be controlled with the variation of chemical potential [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations